2020
DOI: 10.1175/jtech-d-19-0205.1
|View full text |Cite
|
Sign up to set email alerts
|

Correction for Systematic Errors in the Global Dataset of Temperature Profiles from Mechanical Bathythermographs

Abstract: A homogeneous, consistent, high-quality in situ temperature dataset covering some decades in time is crucial for the detection of climate changes in the ocean. For the period from 1940 to the present, this study investigates the data quality of temperature profiles from mechanical bathythermographs (MBT) by comparing these data with reference data obtained from Nansen bottle casts and conductivity-temperature-depth (CTD) profilers. This comparison reveals significant systematic errors in MBT measurements. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…After correcting the systematic errors, the XBT data quality has been improved and the OHC time series show a more homogeneous warming in the half century (Cheng et al, 2018a,b;Goni et al, 2019). In addition to the XBT error, several other sources of uncertainty in OHC estimates have been identified, including MBT biases (Gouretski and Cheng, 2020), mapping methods, and choice of climatology etc. Boyer et al (2016) found that the major source of error in OHC estimates is the mapping method, which defines how the global map of a variable is created from incomplete observations and how the reconstructed field is smoothed.…”
Section: Figure 1 | (A)mentioning
confidence: 99%
“…After correcting the systematic errors, the XBT data quality has been improved and the OHC time series show a more homogeneous warming in the half century (Cheng et al, 2018a,b;Goni et al, 2019). In addition to the XBT error, several other sources of uncertainty in OHC estimates have been identified, including MBT biases (Gouretski and Cheng, 2020), mapping methods, and choice of climatology etc. Boyer et al (2016) found that the major source of error in OHC estimates is the mapping method, which defines how the global map of a variable is created from incomplete observations and how the reconstructed field is smoothed.…”
Section: Figure 1 | (A)mentioning
confidence: 99%
“…The Earth system responds to an imposed radiative forcing through a number of feedbacks, which operate on various different timescales. Conceptually, the relationships between EEI, radiative forcing and surface temperature change can be expressed as (Gregory and Andrews, 2016)…”
Section: Introductionmentioning
confidence: 99%
“…Thus, N TOA represents the difference between the applied radiative forcing and Earth's radiative response through climate feedbacks associated with surface temperature rise (e.g., Hansen et al, 2011). Observation-based estimates of N TOA are therefore crucial both to our understanding of past climate change and for refining projections of future climate change (Gregory and Andrews, 2016;Kuhlbrodt and Gregory, 2012). The long atmospheric lifetime of carbon dioxide means that N TOA , F ERF and T S will remain positive for centuries, even with substantial reductions in greenhouse gas emissions, and lead to substantial committed sea-level rise (Cheng et al, 2019a;Hansen et al, 2017;Nauels et al, 2017;Palmer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Primarily for model verification, we use ocean observation datasets from EN4 (EN.4.2.2, bias corrections .g10, downloaded 2021-01-12) (Good et al, 2013;Gouretski and Reseghetti, 2010;Gouretski and Cheng, 2020) and OSNAP (Lozier et al, 2019;Li et al, 2021).…”
Section: Observational Datamentioning
confidence: 99%